Taylor Made Landscapes: Using Taylor's Law to Scale Between Metapopulations and Source-Sinks in Urban Garden Space - Ong, Theresa W.; Li, Kevin; Lucatero, Azucena; Pak, Damie; Hawkes, L'Oreal; Hunter, MaryCarol; Vandermeer, John (Frontiers in Sustainable Food Systems, 2020)
The structure of terrestrial landscapes is commonly viewed as a problem of statistical description defined by the number, size and distance between habitat patches. Yet, for organisms living in that landscape, structure may be perceived very differently depending on the dispersal capacity of the organism of concern -- large animals may perceive a highly fragmented forest as a single patch if adjacent forest patches are sufficiently close, while small animals may be less likely to disperse across degraded habitat and therefore experience a much different patch structure. This is particularly relevant for fragmented landscapes like cities. Urban gardens are reputed to support a diversity of native and non-native urban species found in urban landscapes. Yet we know little about the long-term persistence of organisms associated with urban gardens. Here we utilize Taylor’s law, a universal scaling law denoting a power law relationship between population size and variance to indicate the synchrony of arthropod populations sampled across time in a fragmented urban landscape. Our results indicate that the utility of urban gardens as habitat is strongly dependent on sampling month, spatial scale and taxon. Constrained dispersal across the landscape may limit the potential of urban gardens to conserve natural enemies including ladybird beetles and parasitoid wasps. In contrast, aphid pests are moving much more freely in the landscape as exhibited through synchrony in abundances sampled across local and landscape scales. We find that regardless of the fragmentation pattern existing in the landscape, short-ranged arthropods are isolated to small, independent garden habitat patches (metapopulation-like) with abundances that oscillate out of sync, while long-ranged species traverse greater distances, synchronizing abundances across large, shared spaces (source sink-like). These results suggest an inherent link between Taylor’s temporal law and metapopulation theory, providing a potential mechanism to explain species-specific slopes of Taylor’s law as arising from the ability of organisms to differentially experience fragmented space along the continuum between metapopulation and source-sink.